The Effect of Exchange Rate Fluctuations on Economic Growth Through the Trade Balance, Inflation and Foreign Debt - Aulia Rahman B; Dara Fitriani Khoirunnisa (Bulletin of Economic Studies (BEST), 2021)
This study describes the effect of exchange rates on the trade balance, inflation, foreign debt, unemployment and economic growth.  Data sourced from BPS and Indonesian Bank. This study uses multiple linear regression analysis. The results of statistical tests show the direct effect of the independent variable on the dependent variable, namely, the exchange rate variable has a negative effect on the trade balance, other than inflation and economic growth in Indonesia.  On the other hand, the effect of the exchange rate on foreign debt has a positive and significant effect. Furthermore, the indirect effect is shown by the effect of exchange rates on the economic growth variable through the trade balance variable which shows the negative effect, then the exchange rate also has a negative effect on economic growth through the inflation rate, and finally the exchange rate has a negative effect on economic growth through foreign debt.  Thus, a serious effort is needed to maintain the stability of the rupiah exchange rate considering its considerable impact on finding that imported raw materials are one of the factors that influence exchange rate fluctuations to become uncontrollable. In addition, the balance of payments deficit is controlled through foreign insurance, not the best solution in maintaining exchange rate stability.Keywords: Exchange Rate, Trade Balance, Inflation, External Debt, Economic Growth